The Influence of Media-Assisted Problem Based Learning with Human Growth Ladder Board Media on Learning Outcomes in Elementary School - Chaerani Rahma Putri; Ervina Eka Subekti; Ikha Listyarini (MIMBAR PGSD Undiksha, 2025)
This study originates from the issue of low student learning outcomes, which are often influenced by conventional teaching practices that tend to be monotonous and the limited use of concrete media that can support conceptual understanding. The main objective of this research is to analyze the influence of the Problem-Based Learning (PBL) model assisted by the Human Growth Ladder Board media on improving elementary students’ learning outcomes. The study employed a pre-experimental approach using a single-group design in which students were engaged in PBL activities supported by simple concrete media designed to visualize human growth concepts more vividly. Data were collected through multiple-choice and open-ended learning achievement tests, as well as observation sheets to assess student engagement during the learning process. Data analysis was carried out statistically by testing distribution normality and identifying differences between pre- and post-learning outcomes. The findings reveal a meaningful improvement in student learning results after the implementation of the PBL model with the Human Growth Ladder Board media. This indicates that problem-based instruction supported by concrete media can strengthen conceptual understanding and enhance active student participation. The study implies the importance of implementing PBL continuously in conjunction with the development of more interactive and contextually relevant learning media to foster meaningful learning and promote higher-order thinking skills.